Hybrid Heteroepitaxial Growth Mode. Issue 8 (10th October 2018) - Burrows, Christopher W.; Hase, Thomas P. A.; Bell, Gavin R.
Abstract : A "hybrid" surface growth mode is studied by in situ scanning tunneling microscopy and ex situ synchrotron X‐ray diffraction. Heteroepitaxial growth of MnSb(0001) on GaAs(111) leads to the direct formation of islands, but the islands themselves grow in a local layer‐by‐layer fashion, having low aspect ratio and flat tops. Strained and relaxed islands co‐exist prior to island coalescence, confirming that dislocation formation occurs locally over a range of average film thicknesses. Abstract : An epitaxial growth mode is studied which combines incomplete wetting of the substrate with locally planar layer‐by‐layer growth. MnSb(0001) grown by molecular beam epitaxy on GaAs(111) forms flat‐topped islands with low aspect ratio. Misfit dislocation density increases steadily with fully strained and partly relaxed islands coexisting.